LPA gene copy number variation and APOE gene polymorphism in young acute myocardial infarction - Mohd Zamri, Iffah Irdhina; Abdullah, Nor Zamzila; A. Talib, Norlelawati; Muhammad Musa, Nurul Ashikin; Abdullah, Aszrin (Kulliyyah of Medicine, International Islamic University Malaysia, Jalan Sultan Ahmad Shah, 25200 Kuantan, Pahang, Malaysia., 2024)
INTRODUCTION: An early onset of acute myocardial infarction (AMI) and a strong family history suggest the possibility of its genetic predisposition. Lipoprotein(a) (LPA) and Apolipoprotein E (APOE) genes are known to be involved in lipid metabolism which may contribute to the development of atherosclerosis leading to AMI. This study aims to assess the association between LPA gene copy number variation (CNV) and APOE gene polymorphism in young AMI patients. MATERIALS AND METHODS: A total of 40 DNAs were extracted from the buffy coat. APOE genotyping and detection of LPA gene CNV were performed using multiplex PCR technique and digital PCR. After tabulation of the results of the current study, meta-analyses were performed from selected studies among Asian populations using the Comprehensive Meta-analysis version 3 software program. RESULTS: No significant association was found between CNV of the LPA gene and the polymorphism of the APOE gene with Young AMI patients in the current study. However, our meta-analysis confirmed that the E4 allele increased the risk for CAD with the E3/E4 genotype [p=0.000, OR= 1.60 (95% CI: 1.41-1.83) significantly increased risk of CAD and individuals with E3/E3 genotype [p=0.000, OR=0.73 (95% CI: 0.66-0.81) were protective against CAD. The gain of LPA CNV was higher in YAMI [n=5 (25%)] than in control [n=2 (10%)] but they are not significant. CONCLUSION: There is no association between the LPA gene CNV and the presence of APOE polymorphism in young AMI, but our meta-analysis confirmed that the E4 allele increased the risk for CAD.